Belhar Confession The Embracing Confession of Faith for Church and Society - Plaatjies-Van Huffel, Mary-Anne (African Sun Media, 2017)
"The subject of the Belhar Confession is an academic one which has enjoyed international attention, with congregations in the West having adopted it as one of their confessions for use. The content of this book is aimed chiefly at a scholarly community with ample knowledge of confessional documents and is a contribution on the subject of the Belhar Confession. The current challenges to the church and theology are discussed. Racism is one issue that poses an increasingly huge challenge to South Africa today. The book demonstrates what needs to be done extra to deal with the scourge of racism that seems to have percolated through virtually all aspects of our existence and particularly the church today in South Africa." - Prof. Rothney Tshaka (University of South Africa)